Evaluation of the H1d flagellin gene targeting pcr for detection of salmonella enterica serovar typhi - Thong, Kwai Lin; Pathmanathan, S.G.; Puthucheary, S.D. (Faculty of Science, University of Malaya, 2005)
A nested-PCR assay targeting the H1-d flagellin gene was evaluated on 46 Salmonella strains representing 27 different serovars and 13 non-Salmonella strains from eight different bacterial genera. The PCR was highly sensitive as it could detect down to 2 cfu/ml after the nested PCR. The first and second round of PCR amplifications produced the expected amplicons in all the S. Typhi as well as S. Muenchen and S. Stanley strains. The second round of PCR also produced an amplicon of the expected size with the Citrobacter freundii strain. These findings indicate that the PCR is not completely specific for S. Typhi. The nested-PCR system also posed problems of carryover contaminations. Although highly sensitive, the problem of specificity and carryover contamination questions the reliability of this nested-PCR assay. Therefore there is a need for the development of new PCR assays targeting more specific regions of the S. Typhi genome.